Viṣṇu’s Strides with Referrence to the Ṛgveda - Sinak, Sanit (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 10 No 1 (2018): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2018)
In Vedic Sanskrit, the Ṛgveda, Viṣṇu did not have the important role. He appeared as a minor deity in the less position. His myths also took place very few in the Vedic texts. By comparison to other gods in the Ṛgveda, there are few stanzas (mantra) which directly praised or prayed for Viṣṇu. In later period of Sanskrit literature, Viṣṇu was described as one god who standed in the highest rank, Trīmūrti god. The main objectives of this article is to survey and collect evident documents which are the important myth of Viṣṇu with special reference to the Ṛgveda by using Thai idiom “the three-position foot-work” (yang sam khum) as the problem of study. The results of the paper found that at present, Thai idiom “the three-position foot-work” is used as one technique of the primary techniques (mae mai muay thai) of Thai boxing. In the Ṛgveda, there are some of mantra-s that are praised or prayed for Visnu as the god who take the three strides covering the whole universe. Three strides of Viṣṇu in the Vedic texts may become source of Thai idiom